2020
DOI: 10.1007/s00062-020-00901-6
|View full text |Cite
|
Sign up to set email alerts
|

Sequelae of Premature Birth in Young Adults

Abstract: Background and Purpose Qualitative studies about the abnormalities appreciated on routine magnetic resonance imaging (MRI) sequences in prematurely born adults are lacking. This article aimed at filling this knowledge gap by (1) qualitatively describing routine imaging findings in prematurely born adults, (2) evaluating measures for routine image interpretation and (3) investigating the impact of perinatal variables related to premature birth. Methods In this study two board-certified radiologists assessed T1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Previous analyses of this dataset using structural MRI include investigations of cortical architecture 7,8,12 , white matter 15,27,28 , subcortical structures 9,10 , and incidental findings on routine brain MRI 76 .…”
Section: Methodsmentioning
confidence: 99%
“…Previous analyses of this dataset using structural MRI include investigations of cortical architecture 7,8,12 , white matter 15,27,28 , subcortical structures 9,10 , and incidental findings on routine brain MRI 76 .…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, the more subtle type, diffuse WMI, remains persistent [ 3 , 4 ]. Diffuse WMI leads to long-term neurodevelopmental and neurobehavioral impairments, resulting in severe cognitive and motor deficits until early adulthood [ 5 , 6 , 7 , 8 ]. The intellectual performance and overall well-being of WMI survivors are limited, leading to high economic and health burdens [ 1 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Beyond the cortex, enlarged ventricles have been reported in radiologic review ( Hedderich et al, 2021 ) and volumetric studies ( Cooke and Abernethy, 1999 ; Stewart et al, 1999 ; Nosarti et al, 2002 ; Kesler et al, 2004 ). Periventricular injury has been linked with neuronal loss in the thalamus and basal ganglia ( Volpe, 2009 ), and MRI studies have shown volumetric reductions in thalamus ( Nosarti et al, 2002 ; Lax et al, 2013 ; Brumbaugh et al, 2016 ; Sølsnes et al, 2016 ; Botellero et al, 2017 ; Sripada et al, 2018 ; Córcoles-Parada et al, 2019 ) and basal ganglia ( Nagy et al, 2009 ; Botellero et al, 2017 ; Karolis et al, 2017 ; Schmitz-Koep et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%